Behavioral Heterogeneity in the Stock Market Revisited: What Factors Drive Investors as Fundamentalists or Chartists?. Issue 1 (13th January 2022) - Li, Leon; Miu, Peter
Abstract: This paper reexamines the issue of behavioral heterogeneity in the stock market. In contrast to previously documented contemporaneous results, we test the issue by identifying and testing four new determinants of the proportion of fundamentalists and chartists in the stock market. Our empirical results are consistent with the following notions. First, the proportion of fundamentalists increases for stocks with incremental information involved in accounting reporting as proxied by discretionary accruals. Second, the proportion of fundamentalists is positively related to the degree of dispersion in financial analysts' forecasts, which implies that stock investors care more about the intrinsic value of firms obtained with fundamental analysis when encountering information asymmetry or uncertainty. Third, the proportion of fundamentalists increases for stocks with higher volatility in prices. For the proportion of chartists, the reverse of these arguments holds true. Fourth, the proportion of chartists versus fundamentalists is related to the investment horizon. Investors give more weights to technical analysis when considering short-term investments. For long-term investments, investors increase the weighting given to the fundamental analysis.